Enuclation Combined with Giant Marsupilization Maxillary Radicular Cyst - Setyawan, Aris; Butarbutar, Kiki Melinda; Samudera, Vega; Yovita, Via; Ariyani, Bitha; Sakuntala, Athalaila (Jurnal Kesehatan - STIKes Prima Nusantara, 2023)
BRadicular cysts are odontogenic inflammatory cysts, which are located at the apex of non-vital teeth. Radiographically, this cyst appears as a round radiolucency with firm borders. Radicular cysts enlarge progressively asymptomatically, until the cyst becomes quite large. This case report discusses a large radicular cyst in the maxilla, which extended from the region of teeth 24 to 13 past the midline of the maxilla. Of the several treatment options available for the treatment of large radicular cysts in the maxilla, the method of enucleation combined with marsupialization and decompression while preserving the bony window as well as extraction of the infected tooth was applied to the patient in this case. This method was chosen with the aim of reducing the size of the cyst cavity and bone tissue defects, as well as triggering the growth of new bone tissue. The procedure was carried out successfully without any complications. Obturator installation was also carried out on the patient, and there was good tissue recovery after surgery